Oxytocin in the prelimbic medial prefrontal cortex reduces anxiety-like behavior in female and male rats - Sabihi, Sara (2014)
The neuropeptide oxytocin (OT) has anxiolytic effects in rodents and humans. However, the specific brain regions where OT acts to regulate anxiety requires further investigation. The medial prefrontal cortex (mPFC) has been shown to play a role in the modulation of anxiety-related behavior. In addition, the mPFC contains OT-sensitive neurons, expresses OT receptors, and receives long range axonal projections from OT-producing neurons in the hypothalamus, suggesting that the mPFC may be a target where OT acts to diminish anxiety. To investigate this possibility, females rats were administered OT bilaterally into the prelimbic (PL) region of the mPFC and anxiety-like behavior assessed. In addition, to determine if the effects of OT on anxiety-like behavior are sex dependent and to evaluate the specificity of OT, male and female anxiety-like behavior was tested following delivery of either OT or the closely related neuropeptide arginine vasopressin (AVP) into the PL mPFC. Finally, the importance of endogenous OT in the regulation of anxiety-like behavior was examined in male and female rats that received PL infusions of an OT receptor antagonist (OTR-A). Overall, even though males and females showed some differences in their baseline levels of anxiety-like behavior, OT in the PL region of the mPFC decreased anxiety regardless of sex. In contrast, neither AVP nor an OTR-A affected anxiety-like behavior in males or females. Together, these findings suggest that although endogenous OT in the PL region of the mPFC does not influence anxiety, the PL mPFC is a site where exogenous OT may act to attenuate anxiety-related behavior independent of sex.